Characterization and Mapping of Soil-Landscape for Site-Specific Soil Management in Ayiba Watershed, Northern Highlands of Ethiopia - Weldemariam Seifu; Eyasu Elias; Girmay Gebresamuel; Gudina Legese Feyisa; Wolde Tefera (Applied and Environmental Soil Science)
The characterization of soil landscapes is becoming increasingly important for making decisions regarding site-specific agriculture systems and soil management. This study was initiated for the purpose of identifying landscape-scale spatial soil variation using a toposequence model so that site-specific fertilization could be achieved. According to the finding, the soils were shallow to very deep in depth, moderately acidic to moderately alkaline in soil reaction, nonsaline in salinity, and clay to sandy loam in texture. The soils were found very low to low levels in most soil nutrients, very low to very high levels of base saturation, and deficient in zinc but have adequate levels of iron, copper, and manganese. The soil exchange complex was mainly dominated by Ca and Mg where the order of occurrence was Ca > mg > K > Na. The CEC values were in high to very high range. Following the field survey and soil analytical results, five main reference soil groups of the World Soil Resource Base—Leptosols (56%), Luvisols (8.5%), Fluvisols (14.4%), Vertisols (13%), and Cambisol (8.2%)—were identified and mapped. Leptosols cover the largest landmass of the watershed and mostly found at the summit and hill back slopes. On the other hand, Luvisols, Fluvisols, Vertisols, and Cambisols were found on the middle and foot slopes. According to the findings, the variation in soil source indicating that topography is the primary pedogenic element in the formation of the soil in the watershed that was under research. Therefore, having local-scale-specific soil information can assist the site-specific application of soil nutrients and amendments based on spatial variability which is tailored to the soil requirements.